COMMENT ON NUTRITIONAL STATUS IN THE RURAL POPULATION - THROUGH SOME INDIVIDUAL INDICATORS (Vietnam Journal of Community Medicine, 2021)
Objective: Describe the nutritional status of the elderly in rural Thai Binh provinceStudy subjects: the elderly from 60-74 years old in 4 rural communes in two districts (Vu Thu and Kien Xuong).Research method: Epidemiological method described through cross-sectional investigation with analysis.Research results: Research results show that high projection, average weight of age groups decreases with age. Mean BMI values ​​of the elderly, men and women in the age group 60-64 and 70-74 differ. The rate of chronic energy deficiency (TNLTD) and overweight and obesity among the elderly women is higher than that of men. The rate of the elderly lack of staged energy and specialized care in Vu Thu area is higher than in Kien Xuong. The proportion of people with high TCBP age (BMI≥25) in Kien Xuong was 9.5%, higher than 6.7% in Vu Thu. The percentage of body fat for men (30.2%) is lower than that of women (41.8%) with p
Keywords: Nutrition, elderly, anthropometric index, Thai Binh